Familial misophonia or selective sound sensitivity syndrome : evidence for autosomal dominant inheritance? - Sanchez,Tanit Ganz (2018)
Abstract Introduction: Misophonia is a recently described, poorly understood and neglected condition. It is characterized by strong negative reactions of hatred, anger or fear when subjects have to face some selective and low level repetitive sounds. The most common ones that trigger such aversive reactions are those elicited by the mouth (chewing gum or food, popping lips) or the nose (breathing, sniffing, and blowing) or by the fingers (typing, kneading paper, clicking pen, drumming on the table). Previous articles have cited that such individuals usually know at least one close relative with similar symptoms, suggesting a possible hereditary component. Objective: We found and described a family with 15 members having misophonia, detailing their common characteristics and the pattern of sounds that trigger such strong discomfort. Methods: All 15 members agreed to give us their epidemiological data, and 12 agreed to answer a specific questionnaire which investigated the symptoms, specific trigger sounds, main feelings evoked and attitudes adopted by each participant. Results: The 15 members belong to three generations of the family. Their age ranged from 9 to 73 years (mean 38.3 years; median 41 years) and 10 were females. Analysis of the 12 questionnaires showed that 10 subjects (83.3%) developed the first symptoms during childhood or adolescence. The mean annoyance score on the Visual Analog Scale from 0 to 10 was 7.3 (median 7.5). Individuals reported hatred/anger, irritability and anxiety in response to sounds, and faced the situation asking to stop the sound, leaving/avoiding the place and even fighting. The self-reported associated symptoms were anxiety (91.3%), tinnitus (50%), obsessive-compulsive disorder (41.6%), depression (33.3%), and hypersensitivity to sounds (25%). Conclusion: The high incidence of misophonia in this particular familial distribution suggests that it might be more common than expected and raises the possibility of having a hereditary etiology.